SISTEM PAKAR IDENTIFIKASI PSIKOPAT DENGAN METODE FORWARD CHAINING BERBASIS WEB - Irwandi, Irwandi; Richardo, Kenny; Hartono, Wira Jaya (International Journal of Business and Information Technology, 2021)
Psychopaths (Antisocial Personality Disorder) are mental disorders that can be used as a reference to create an expert system. The purpose of this research is to design and build an expert system to identify psychopaths with a web-based forward chaining method and to analyze and find out the symptoms of a psychopath in order to make sufferers and society feel at ease. The type of data used in this study is qualitative data which emphasizes the description of the process and words rather than the results such as the results of mathematical calculations or in the form of numbers. The author has several conclusions that expert systems can replace the role of experts who can provide suggestions or problem solutions to users, expert systems are often made using the PHP and MySQL programming languages, and the forward chaining method is suitable for use in web-based psychopath identification expert systems. This is because by asking questions first, conclusions can be drawn from the problem. The suggestions for the next researchers are the development of this software becomes practical for users, this web-based psychopath identification expert system can be created into android-based and an expert system in order to make it more and more practical because it relates to the cure of human soul.